Bentuk Perlindungan dan Mekanisme Kompensasi atas Pengakhiran Kontrak Sepihak oleh Kurator - Muhammad Dzaki Alfathur; Putu Samawati Saleh; Helena Primadianti Sulistyaningrum (Fakultas Hukum, Universitas Sains dan Teknologi Komputer, 2026)
Lease agreements entered into before the pronouncement of a bankruptcy order by the judge are often unilaterally terminated by the liquidator, thereby creating a tension between the principle of pacta sunt servanda in contract law and the liquidator’s powers under the Bankruptcy and Debt Repayment Moratorium Act. Consequently, tenants acting in good faith sometimes suffer losses and see their legal status change to that of a concurrent creditor subject to the pari passu prorate parte principle. The objective is to clarify the form of protection and compensation mechanisms available to tenants following the unilateral termination of a lease agreement by the liquidator. This paper analyses the issue using a normative legal research method with a legislative, conceptual, and analytical approach to examine the provisions of the Civil Code alongside the Bankruptcy Act and the PKPU. The research findings indicate that pre-bankruptcy lease agreements remain valid, but their binding force is conditional and subject to the bankruptcy regime. Unilateral termination by the trustee transforms the tenant’s status into that of a concurrent creditor. Although a mechanism for compensation is available through the submission of claims for costs and damages, its realisation is highly dependent on the availability of the bankrupt’s assets and the principle of proportional distribution. Therefore, the presence of a Supervising Judge is crucial to ensuring justice for tenants acting in good faith.